Perencanaan Preservarsi Jalan Arosbaya Campor Kabupaten Bangkalan - Jaya, Heri Prasetya; Qordhowi, Andrian Firdaus Yusuf Al; Sudarso, Sudarso (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The suboptimal condition of road infrastructure remains a challenge in many regions, including the Arosbaya–Campor road segment in Bangkalan Regency. This road is mostly composed of red earth, which is highly vulnerable to damage caused by rainfall and traffic loads, reducing comfort and safety for road users. This study aims to analyze the existing road condition using the Surface Distress Index (SDI) method and to formulate a road preservation strategy based on technical and social data. A descriptive qualitative approach was applied through field surveys, documentation, interviews, and Pavement Condition Index (PCI) analysis. The results indicate that the road is categorized as lightly damaged, with SDI values ranging from 50% to 70%. Based on a CBR value of 6.15% and an Average Daily Traffic (ADT) of 781 vehicles, pavement thickness was designed using the 2017 Pavement Design Manual (MDP). The recommended structure includes a 40 mm AC-WC layer, 60 mm AC-BC layer, and 400 mm Class A aggregate base for road widening, while the existing pavement requires a 40 mm AC-WC overlay.